The Lost Life of Ira Daniel Aldridge (Part 1) - Lindfors, Bernth (Text Matters: A Journal of Literature, Theory and Culture, 2012)
The sons of famous men sometimes fail to succeed in life, particularly if they suffer parental neglect in their childhood and youth. Ira Daniel Aldridge is a case in point-a promising lad who in his formative years lacked sustained contact with his father, a celebrated touring black actor whose peripatetic career in the British Isles and later on the European continent kept him away from home for long periods. When the boy rebelled as a teenager, his father sent him abroad, forcing him to make his own way in the world. Ira Daniel settled in Australia, married, and had children, but he found it difficult to support a family. Eventually, he turned to crime and wound up spending many years in prison. The son of an absent father, he too became an absent father to his own sons, who also suffered as a consequence.